2007
DOI: 10.1158/0008-5472.can-07-2142
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Markers in Breast Cancer: Coexpression, Relationship with Pathologic Characteristics, and Risk Factor Associations in a Population-Based Study

Abstract: The objective of this study was to evaluate the coexpression patterns of hormonal markers in breast cancer tissue and their relationship with pathologic characteristics and epidemiologic risk factors. We evaluated the expression of 17 markers by immunohistochemistry in 842 invasive breast carcinomas collected in a population-based case-control study conducted in Poland. Based on marker correlations, factor analysis identified four major coexpression patterns ( factors): ''nuclear receptor factor'' [estrogen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 32 publications
2
37
3
Order By: Relevance
“…It should be noted that the number of cases of IDC evaluated in this study was small (n ϭ 29). A recent paper in a population based study (n ϭ 698) on hormonal markers in breast cancer identified a significant correlation ( p Ͻ 0.01, Pearson correlation coefficient ϭ 0.14) between CYP19 and CYP1B1 (Yang et al, 2007). We believe that the likely reason for the difference in results between this study and ours is sample size, with the larger study (Yang et al, 2007) having greater power to detect this correlation.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…It should be noted that the number of cases of IDC evaluated in this study was small (n ϭ 29). A recent paper in a population based study (n ϭ 698) on hormonal markers in breast cancer identified a significant correlation ( p Ͻ 0.01, Pearson correlation coefficient ϭ 0.14) between CYP19 and CYP1B1 (Yang et al, 2007). We believe that the likely reason for the difference in results between this study and ours is sample size, with the larger study (Yang et al, 2007) having greater power to detect this correlation.…”
Section: Discussioncontrasting
confidence: 65%
“…A recent paper in a population based study (n ϭ 698) on hormonal markers in breast cancer identified a significant correlation ( p Ͻ 0.01, Pearson correlation coefficient ϭ 0.14) between CYP19 and CYP1B1 (Yang et al, 2007). We believe that the likely reason for the difference in results between this study and ours is sample size, with the larger study (Yang et al, 2007) having greater power to detect this correlation. In another study (Esteban et al, 1992), a significant ( p ϭ 0.04), but inverse correlation between CYP19 and ER immunoreactivity was reported, indicating a likelihood of detecting CYP19 in ER-negative tumors.…”
Section: Discussioncontrasting
confidence: 65%
“…Although none of the older epidemiologic studies were designed to identify risk factors by molecular subtype, recent post hoc reanalyses also raise interesting questions about traditional risk factors and whether some risk factors are stronger for one subtype versus another or even have opposite effects in different subtypes. For example, in contradistinction to luminal breast cancer, higher parity and young age at first birth may be risk factors for basal-like breast cancer, whereas lack of breast feeding and early age of menarche may be stronger risk factors than for luminal breast cancers (41,43,44). Given our understanding of breast cancer as a heterogeneous disease, further research will need to focus on examination of individual risk factors within subtypes.…”
mentioning
confidence: 99%
“…In each field, 200 cancer cells were counted (10,000 cells total), and the proportion of positive cells was calculated. Semi-quantitation was performed as previously reported 16 . In brief, quantitation was based on the staining intensity and the proportion of positive cells.…”
Section: Immunohistochemistry Evaluationmentioning
confidence: 99%